Exploration of Medicinal Plants Utilized by Indigenous Papuans in Arfak Mountains Regency - Maturbongs, Agatha Cecilia; Sinipar, Fajar Ria Dwi Natalia; Lefaan, Paskalina Theresia; Sutarno, Simon; Budirianto, Heru Joko; Kilmaskossu, Johanis Paulus; Maturbongs, Rudi Aprianto; Sadsoeitoeboen, Maria Justina; Susanto, Slamet Arif; Ahoren, Linda (Universitas Cokroaminoto Palopo, 2025)
This study aimed to explore the use of plants as traditional medicine by indigenous Papuans in the Arfak Mountains. The local population residing in the villages of the Arfak Mountains primarily consists of the Arfak tribes, including the Hatam, Sough, and Meyah. These communities have traditionally relied on local plants to address various health issues. The research employed a descriptive method, incorporating interviews and direct field surveys. Respondents were selected based on their extensive knowledge of medicinal plant use. The results revealed that 20 plant species are utilized by the local population to treat a range of health conditions. These include coughs, colds, fevers, flatulence, itching, boils, malaria, external wounds, hypertension, body aches, internal pain, lumps, fertility issues, facilitation of childbirth, and ailments attributed to witchcraft. Some plants are used individually, while others are combined with different plants. Processing methods include mashing, boiling, or squeezing to extract the liquid. Utilization methods involve drinking, chewing and swallowing the juice, or applying it to affected areas. The plant parts used include leaves, stems, tubers, and flowers.